Over-specification of small, borderline cardinalities and color in referential communication: the role of visual context, modifier position, and consistency - Zevakhina, Natalia A.; Dongarova, Kseniya N.; Shubina, Daria; Popova, Daria P. (Frontiers in Psychology, 2024)
This paper reports on two flash-mode experiments that test redundant descriptions of small (2–4) cardinalities, borderline (5–8) cardinalities, and color in referential communication. It provides further support for the idea that small cardinalities are more salient (due to subitizing), less sensitive to visual context, and therefore give rise to higher over-specification rates than color. Because of greater salience, Russian speakers more often use prenominal positions for numerals than for color adjectives. The paper also investigates borderline cardinalities and argues for the order factor that affects their salience, since ordered items can be perceived in small subitized parts. The ordered mode of presentation of the borderline cardinalities leads to higher over-specification rates and to higher percentages of prenominal positions than the unordered one. The paper provides further evidence for the consistency of small, borderline cardinalities, and color in people’s choices to minimally specify or over-specify given objects in referential communication.